2014
DOI: 10.1007/s10765-014-1677-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Temperatures of High-Temperature Fixed Points: Uncertainties Due to Temperature Drop and Emissivity

Abstract: This study forms part of the European Metrology Research Programme project implementing the New Kelvin to assign thermodynamic temperatures to a selected set of high-temperature fixed points (HTFPs), Cu, Co-C, Pt-C, and Re-C. A realistic thermal model of these HTFPs, developed in finite volume software ANSYS FLUENT, was constructed to quantify the uncertainty associated with the temperature drop across the back wall of the cell. In addition, the widely applied software package, STEEP3 was used to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In effect, it is the temperature drop across the thickness of the cavity (back) wall. As it is impossible to know with precision what that thickness is after cell construction and as this effect is similar for all furnaces and for all cells [16,42,43], no correction has been applied for temperature drop. The estimated uncertainty, taken to be the full value of the calculated temperature drop, is given in table 3.…”
Section: (B) Temperature Dropmentioning
confidence: 99%
See 4 more Smart Citations
“…In effect, it is the temperature drop across the thickness of the cavity (back) wall. As it is impossible to know with precision what that thickness is after cell construction and as this effect is similar for all furnaces and for all cells [16,42,43], no correction has been applied for temperature drop. The estimated uncertainty, taken to be the full value of the calculated temperature drop, is given in table 3.…”
Section: (B) Temperature Dropmentioning
confidence: 99%
“…It has been observed that use of different furnaces can affect the realized (point of inflection) melting temperature of a HTFP, e.g. [16,18]. Different furnaces were used by the participants.…”
Section: Furnace Effectmentioning
confidence: 99%
See 3 more Smart Citations